Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Vickie Savaria, Tomar Mason, Val Weston at check-in table 5080 E. Kings Canyon Road, Fresno